Specific features of current intraperitoneal therapy in patients with ovarian cancer - A. G. Kedrova; S. A. Levakov; S. E. Krasil'nikov; T. A. Maksimenko; V. I. Voznesenskiy; A. V. Gerasimov; D. A. Astakhov; V. V. Kosyy; O. E. Nechaeva (ABV-press, 2016)
Background. Today there are 3 trends in favor of intraperitoneal (IP) chemotherapy: maintenance of its potential 5- and 10-year survival benefit in patients with ovarian cancer (OC); advantages of the IP administration of drugs even after nonoptimal surgery; enhancement of the efficiency of chemotherapy irrespective of the number of IP treatment cycles. There is also an expanded list of possible IP medicines and incorporation of novel targeted drugs into treatment regimens. However, the long-expected data of the most recent randomized trial GOG 0252 have proven deplorable and led to the activation of discussions on the role of IP therapy.Objective: to generalize the experience of 4 oncology departments with IP therapy in patients with disseminated OC and to compare the findings with those obtained by the world's leading medical centers.Materials and methods. The retrospective analysis included 76 patients with Stage IIIC OC who had received IP chemotherapy in accordance with 3 regimens. For standardization of IP treatment procedures, the investigators assessed the following indicators: age; tumor morphological type; surgical radicality; catheter model and port placement procedure; drug administration route; number of treatment cycles; efficiency of therapy from expert ultrasonographic findings and CA-124, HE4, CA-19.9 marker levels, time to disease progression. The analysis also involved adverse manifestations, methods of their correction and the reasons for early treatment discontinuation were separately reported. The obtained data were processed using standard statistical programs.Results. 55 of the 76 patients could complete more than 4 IP therapy cycles. Among them, only 4 patients were observed to have disease progression at follow-ups lasting over 24 months.Conclusion. Current IP therapy is a safe and convenient drug treatment in patients with OC after optimal cytoreductive surgery. The mastery and standardization of the procedures for surgery and placement of current IP Celsite® Peritoneal and Celsite® Drainaport devices make it possible to minimize adverse manifestations and to perform all planned therapy cycles in necessary mode, by giving 50 % of the optimally operated patients with OC (Stage IIIC) the chance to have a long-term progression-free survival that is over 2 years, as shown by our observations.